Scribbles and Ink : the contest - Long, Ethan (Blue Apple Books, 2013)
"Scribbles the cat and Ink the mouse are buddies and fellow artists. When they enter a 'Draw a Dinosaur' contest, shenanigans ensue as their artistic creations come to life"--